Quantum information storage and state transfer based on spin systems - Song, Z.; Sun, C.P. (Физика низких температур, 2005)
The idea of quantum state storage is generalized to describe the coherent transfer of quantum
information through a coherent data bus. In this universal framework, we comprehensively review
our recent systematical investigations to explore the possibility of implementing the physical processes
of quantum information storage and state transfer by using quantum spin systems, which
may be an isotropic antiferromagnetic spin ladder system or a ferromagnetic Heisenberg spin
chain. Our studies emphasize the physical mechanisms and the fundamental problems behind the
various protocols for the storage and transfer of quantum information in solid state systems.